Study on Effectiveness and Outcomes of Educational Inhaler Technique Counselling in Respiratory Department by Clinical Pharmacist - Thakkar, Kavit; Patel, Rohan; Abraham, Rinchu; Shah, Arti; Rajput, Hemrajsingh; Chandrakar, Vikas (Journal of Pharmacy Practice and Community Medicine)
Background: The correct inhalation technique is a crucial factor governing the efficiency of inhaled medication and is critical in ensuring optimal medication conveyance to the lungs. It is imperative to use the inhaler properly and to have sufficient knowledge, so we conducted this study to assess technique and provide education on Inhaler techniques in patients with respiratory disease. Materials and Methods: A Cross-sectional interventional study was conducted at the Department of Respiratory Medicine, Dhiraj Hospital, Vadodara, from October 2019 to March 2020. The inhalation technique was evaluated by specific checklist (NHS Liverpool Clinical Commissioning Group- inhaler device checklist). Patients having incorrect inhaler techniques were counselled along with physical demonstration of the proper inhaler technique. A pre-and post-intervention score was compared to evaluate the benefit of the intervention. Results: A total of 120 patients were enrolled in the study. Before counseling, 11.67%, 58.33%, and 30% of patients had poor, moderate, and good inhaler technique, respectively, while post counseling, 87.50%, 12.50%, and 0% had good, moderate, and poor inhaler technique, respectively. Pearson correlation coefficient (r) value of 0.6686 depicts strong positive correlation between pre-and post-intervention mean scores with significant p-value. Literacy and age showed considerable impact on inhaler techniques. Conclusion: Overall, the majority of patients had erroneous inhaler technique, however after counseling a dramatic surge in the number of patients having correct inhaler technique was beheld, which suggests that clinical pharmacist’s frequent counselling is indispensable and can improve efficacy and therapeutic outcomes.
Keywords: Asthma; COPD; Respiratory; Inhaler; Intervention; NHS checklist.